Region Housing Policies in Terms of its Social and Economic Security - Onyshchenko, Volodymyr; Kozachenko, Anna; Zavora, Taina (International Journal of Engineering and Technology, 2018)
The basics of the state housing policies formation are explored. Analysis of the housing policies formation directions in terms of transformational changes is conducted. Connection between economic and social spheres in the context of region social and economic security providing is substantiated. Special aspects of housing policies impact on region social and economic security formation are defined. Simulation of housing policies impact on region social and economic security is conducted. Integral estimation of housing policies is developed and its connection with some of the principal regional development social and economic indices is analyzed. Correlational relationships between the received housing policies integral estimation and such indices as household income, personal expenditures on goods and services purchasing, population income differentiation R/P 10%, proportion of population with lower monthly income per capita than enacted living wages,Â correlation between monetary income of the most and the least haves 10% of population, and number of sicknesses. Dependence between people income from relative indices such as housing resources in average per capita and capital investment into house building is defined.Â Â